Políticas públicas de transformação digital : os processos de mudança e a formação da agenda - Moura, Luzia Menegotto Frick de (2022)
Society undergoes transformations throughout its evolution, bringing about social, process, and technological changes. One contemporary movement is Digital Transformation (TD), which affects people and organizations. In this paper, the focus of TD is on public administration, with a look at public policies (PP) related to the theme. The objective of the work is to understand which themes instigate the formulation of the public policy agenda of digital transformation in Brazil. Thus, based on the understanding of the PPs from the public policy cycle, the work has a focus on the actors, seeking, through narrative, to understand the themes that guide the TD PP agenda. To achieve the objectives, this work used the Thematic Analysis method. Narrative interviews were conducted so that the researcher had the least possible bias, seeking emerging themes according to the speeches. From this, and the themes found, it was possible to identify similarities with other theories. In direct relation to Digital Transformation, it was possible to identify that Brazil is going through a DT, still very much based on the digitalization of services, despite being in the process of structural change. It was also identified the need to reformulate processes, making them more dynamic and flexible, which goes against the traditionally bureaucratic and compartmentalized public organizations. Finally, it was also possible to identify themes that corroborate with Kingdon's Multiple Streams Model (2003), which focuses on the actors involved in the formation of the public policy agenda. Thus, it was possible to identify relevant points for agenda formation in TD PP, which accelerated with the COVID19 pandemic, but are also aligned with the principles of New Public Management, reflected by the Brazilian state reform in the 1990s.